PENGARUH PERMAINAN EDUKATIF ULAR TANGGA TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI PECAHAN SISWA KELAS V SDN OESAPA KECIL 2 - Bikolo, Maria Ferdiana; Hendrik, Hingrida Margarita Anastasia; Nitte, Yulsy Marselina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low mathematics learning outcomes of grade V students of SDN Oesapa Kecil 2 in fractional materials. The learning process, which is still dominated by lecture methods and the lack of the use of interesting learning media, causes students to be less active and easily feel bored in participating in learning. This study aims to determine the influence of the snake and ladder educational game on mathematics learning outcomes in fractional material of grade V students of SDN Oesapa Kecil 2. The research method used is quantitative research with a pre-experimental type using the One Group Pretest-Posttest design. The research sample amounted to 28 students in grade V of SDN Oesapa Kecil 2. Data collection techniques are carried out through observation, tests, and documentation. The research instruments are in the form of pretest and posttest questions that have been tested for validity, reliability, differentiation, and difficulty. Data were analyzed using normality tests, hypothesis tests, and N-Gain tests. The results of the study show that the use of educational games of snakes and ladders has a positive influence on students' mathematics learning outcomes in fractional materials. This is shown by the increase in student learning outcomes after being treated using the snake and ladder educational game. In addition, students become more active, enthusiastic, and enthusiastic in participating in mathematics learning. Thus, the snake and ladder educational game can be used as an effective learning medium to improve the mathematics learning outcomes of elementary school students, especially in fractional materials.